A Comparative Study of Perceived Importance and Preparedness of Soft Skill Competencies among Final-Year Hospitality Students and Early Career Employees in Mumbai Star Hotels ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2026)
Background: Soft skills such as communication, leadership, teamwork, time management and problem-solving are increasingly recognized, are becoming more critical for successful hospitality businesses. Mumbai’s star hotels, where expectation for service standards is high have close link with hospitality education to produce skilled professionals. Objectives: This study compares final-year hospitality students’ perceptions of soft-skill importance and preparedness with early-career employees’ retrospective evaluations of their perceptions of soft-skill importance and readiness. The study also highlights the potential gaps between academic training and workplace realities. Methodology: A comparative quantitative design was employed, surveying 98 final-year students and 84 early-career employees in Mumbai using structured questionnaires. Responses were measured on a five-point Likert scale. Data analysis included descriptive statistics, paired samples t-tests and independent samples t-tests. Results: Both groups rated soft skills as highly important (mean > 4.0). However, through paired sample test the preparedness scores were consistently lower, with lowest reporting mean for readiness (M=3.85) for communication and the highest reported mean of preparedness being (M = 3.96) for both time-management and problem-solving. Significant differences appeared between importance and preparedness within both groups, but no significant differences were found between students and employees in overall perceptions. Conclusion: Findings reveal a persistent gap between the recognized importance of soft skills and perceived preparedness among hospitality graduates and employees. While academic training aligns with industry expectations in recognizing importance, practical readiness remains insufficient. The study highlights the need for experiential learning, industry collaboration and curriculum reforms to strengthen soft-skill development in hospitality education.
Keywords: Hospitality education, soft skills, preparedness, Mumbai star hotels,experiential learning, industry collaboration